A method for designing control parameters of a 3-DOF parallel tool head. (February 2017) - Wang, Dong; Wu, Jun; Wang, Liping; Liu, Yuzhe; Yu, Guang
Abstract: The mechatronic system of a parallel tool head consists of the mechanical subsystem and the control subsystem, and appropriate control parameters have a significant effect on the performance of the parallel tool head. Thus, it is a core issue of how to make the right choice of the control parameters. However, due to the time-varying and coupling dynamic characteristics, there is still not an effective control parameters design method during industrial machining process. In this paper, by taking a 3-DOF parallel tool head with proportional control and velocity feedforward compensation as an object of study, a complete method for designing control parameters is investigated. First, a coupling variable is specified to reflect the dynamic properties between the mechanical subsystem and the control subsystem. Next, a novel dynamic index is proposed to evaluate the dynamic load of each driving shaft in the workspace, and the shaft with maximum dynamic load should be mainly pay attention. Then, based on the typical movement experiments, two design indices are proposed to ensure that the coupling variable has appropriate properties during the motion process. Finally, a parameters design experiment and a cutting experiment of an S-shaped test piece are performed, the results show that compared with the original control parameters used in industry, the tracking error of the driving shaft is much better when using the optimized control parameters, and the test piece meets the accuracy requirement. This design thought can also be applied to other parallel manipulators in industry.